Identification, Structural and Functional Characterization of Dormancy Regulator Genes in Apricot (Prunus armeniaca L.) - Balogh, Eszter; Halász, Júlia; Soltész, Alexandra; Erös-Honti, Zsolt; Gutermuth, Ádám; Szalay, László; Höhn, Mária; Vágújfalvi, Attila; Galiba, Gábor; Hegedüs, Attila (Frontiers in Plant Science, 2019)
In the present study, we identified and characterized the apricot (Prunus armeniaca L.) homologs of three dormancy-related genes, namely the ParCBF1 (C-repeat binding factor), ParDAM5 (dormancy-associated MADS-BOX) and ParDAM6 genes. All highly conserved structural motifs and the 3D model of the DNA-binding domain indicate an unimpaired DNA-binding ability of ParCBF1. A phylogenetic analysis showed that ParCBF1 was most likely homologous to Prunus mume and Prunus dulcis CBF1. ParDAM5 also contained all characteristic domains of the type II (MIKCC) subfamily of MADS-box transcription factors. The homology modelling of protein domains and a phylogenetic analysis of ParDAM5 suggest its functional integrity. The amino acid positions or small motifs that are diagnostic characteristics of DAM5 and DAM6 were determined. For ParDAM6, only a small part of the cDNA was sequenced, which was sufficient for the quantification of gene expression. The expression of ParCBF1 showed close association with decreasing ambient temperatures in autumn and winter. The expression levels of ParDAM5 and ParDAM6 changed according to CBF1 expression rates and the fulfilment of cultivar chilling requirements. The concomitant decrease of gene expression with endodormancy release is consistent with a role of ParDAM5 and 6 genes in dormancy induction and maintenance. Cultivars with higher chilling requirements and delayed flowering time showed higher expression levels of ParDAM5 and ParDAM6 toward the end of endodormancy. Differences in the timing of anther developmental stages between early- and late-flowering cultivars and two dormant seasons confirmed the genetically and environmentally controlled mechanisms of dormancy release in apricot generative buds. These results support that the newly identified apricot gene homologs have a crucial role in dormancy-associated physiological mechanisms.